Health-Seeking Behavior and Quality of Life of People Living With HIV: Novel Evidence From Ghana - Benjamin Spears Ngmekpele Cheabu MSc; Naasegnibe Kuunibe PhD; Paul Kwame Nkegbe PhD; Peter Yeboah MSc; James Duah MD, MPH; Joseph Kwaku Addae MSc; Francis Adjei Osei PhD; Ignatius Terence Ako-Nnubeng MPhil; Kafui Senya MD (Journal of the International Association of Providers of AIDS Care, 2023)
The health and economic burdens of HIV/AIDS in low-and-middle-income countries are enormous despite global and local efforts to prevent and mitigate its effect. This study seeks to assess cadres’ (or people living with HIV [PLHIV]) health-seeking behavior and its effects on their quality of life (QoL). We collected cross-sectional data from 218 HIV community cadres and 255 noncadres in 11 out of the 16 political regions in Ghana based on a modified WHOQOL-HIV-Brief and EQ-5D questionnaires. We used descriptive statistics to describe the sample and calculate the QoL scores. We also used regression analysis (ordered logit and ordinary least squares) to analyze the factors associated with the QoL of our respondents. We found that women (77%) are still disproportionally affected by HIV. Similarly, the youth, less educated and informal sector employees continue to be affected most by HIV. Factors related to QoL of PLHIV include being a community cadre, health-seeking behavior, comorbidities, and employment type. We recommend that alternative health providers be educated on the basic science of HIV/AIDS to help them offer appropriate support to PLHIV who visit them for care. Additionally, PLHIV should be supported to engage in less energy demanding employment options.